Relevance of oil prices for mobility today and in the next decades - Andreas Seeliger (Mobility in a Globalised World, 2012)
The paper discusses the role of crude oil prices as an important cost factor for individual and collective mobility. After a short introduction, there will be three further sections. Section 2 covers a general discussion of the relevance of oil today and also several scenarios for the future demand development will be discussed. In section 3 some oil price forecasts will be presented and compared to fundamental cost parameters. The paper ends with a conclusion section.
urn:nbn:de:101:1-2020110913255942662816
Keywords: Q41; Q47; 330; Oil prices; Energy markets